THE INFLUENCE OF SERVICE QUALITY AND CUSTOMER SATISFACTION ON DECISIONS TO PURCHASE FOOD PRODUCTS AT UD MARIANI SURABAYA - Imam Sultan Rifaldy; Is Fadhilah (Pedagogic Research-Applied Literacy Journal, 2025)
This study aims to determine the effect of service quality and customer satisfaction on purchasing decisions on basic food products at UD. Mariani. Service quality and customer satisfaction are measured through various aspects, such as service speed, friendliness, and product suitability to customer needs. While purchasing decisions are analyzed by considering the frequency of purchases and customer loyalty to basic food products sold at UD. Mariani, the research method used is quantitative with a survey approach where data is collected through questionnaires distributed to customers who shop at UD. Mariani, the data analysis technique used is multiple linear regression to test the effect of independent variables on dependent variables. The results of the study indicate that service quality has a positive and significant effect on purchasing decisions, as well as customer satisfaction, which also has a positive effect on purchasing decisions for basic food products. These findings indicate that improving service quality and customer satisfaction can improve purchasing decisions at UD. Mariani, which can ultimately support the sustainability of the company’s business.